Pengembangan Modul Ajar IPAS Berbasis Kooperatif Team Accelerated Instruction untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD - Nila Dwi Susanti (Yayasan Literasi Altruis Khatulistiwa, 2026)
This study aims to develop a Natural and Social Sciences (IPAS) teaching module based on the Team Accelerated Instruction cooperative model and to determine the level of validity, practicality, and effectiveness of the teaching module in improving the learning outcomes of fourth-grade elementary school students. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were 28 fourth-grade students of SDN Ngasem I Bojonegoro. Data collection techniques were carried out through expert validation sheets, student response questionnaires, observation sheets of learning implementation, and learning outcome tests. Data were analyzed descriptively quantitatively and qualitatively. The results showed that the Team Accelerated Instruction-based IPAS teaching module had a validity level of 90% with a very valid category, a practicality level of 88% with a very practical category, and was effective in improving student learning outcomes. This is demonstrated by an increase in the average learning outcome score from 67 on the initial test to 85 on the final test, as well as an increase in classical learning completion from 50% to 93%. Based on these results, it can be concluded that the science learning module based on the Team Accelerated Instruction cooperative model is suitable for use as a teaching material to improve the learning outcomes of fourth-grade elementary school students.